SOME MANOEUVRES FOR RELEASING THE HYPERTONUS OF SPASTIC AND SHORTENED MUSCLES - Mayer, Michal; Grulichova, Jitka; Bazala, Josef (Biomedical papers, 1999)
We describe some physiotherapeutic techniques and manoeuvres releasing the increased tone of spastic andshortened muscles. The techniques can be generally characterised and summed up into three groups as follows:I. First types of manoeuvres consists in setting up the extremity or segment into the position usually opposed orantagonistic to the limited direction. This position is held for several tens of seconds. After this, partial of theoriginally limited range of motion could be observed. A modification of this approach is effective for persistentextensor spasticity of the lower extremities. Extremity is taken up into the internal rotation and flexion of the hipjoint, into the maximal flexion of knee joint and into dorsiflexion of ankle joint, and this position is held at least for30 seconds. After this, the extensor spasticity is usually diminished and also the voluntary movements and gaitpattern improved.II. Short active jerk (not exceeding 1/2 sec) in the free direction, alternatively against mild resistance, followedby 3-4 second release and slow stretch into the restricted range. It is essentially important that the initial jerk is asbrisk as possible but performed with no especial effort. In case the resistance is applied, it should be only slight.Then the therapist must grasp a ``melting'' of the hypertonus and cautiously guide the segment into the slow andgentle stretch.III. Pressure stimulation of the particular active zones.The application of these manoeuvres and its combinations are demonstrated in case reports.
Keywords: Spasticity / Shortened Muscles / Therapy / Physiotherapy / Kinesitherapy / Rehabilitation